AI business strategy : a managerial guide to success - Hutzschenreuter, Thomas; La??mmermann, Tim (Routledge, 2026)
"This book equips you with essential knowledge to strategically adopt and leverage today's machine learning-based AI systems. Drawing on several years of research with globally leading corporations, it provides an innovative guide to developing your own AI business strategy. It is packed with diverse strategy examples and hands-on worksheets to help you turn newly gained insights into immediate, practical action"-- Provided by publisher.